A fuzzy-based pulse-width modulation (PWM) control for low speed autonomous emergency braking (AEB) system: A mini-fuzzy associative matrix (FAM) approach - Baldovino, Renann G. (Animo Repository, 2017)
Autonomous emergency braking (AEB) system is a vehicle safety technology used in preventing or avoiding vehicles from crash or mitigate the impact brought by crash. This system can be used to apply brakes independently of the driver if the situation becomes problematic. In this study, an intelligent based AEB control algorithm was developed using fuzzy-based pulse-width modulation (PWM) technique. ‘Mini’ fuzzy associative matrix (FAM) table algorithm was introduced to reduce the number of computational rules. For the feedback system, an ultrasonic sensor was used to monitor and detect the distance of a certain obstacle. Moreover, the PWM output were applied to the DC motor for the main actuation and the LED light, together with the buzzer for the activation of the alarm system. © 2017 American Scientific Publishers All rights reserved.